2022
DOI: 10.3390/ani12162133
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium, Haplotype Block Structures, Effective Population Size and Genome-Wide Signatures of Selection of Two Conservation Herds of the South African Nguni Cattle

Abstract: The Nguni cattle of South Africa are a Sanga breed, characterized by many eco-types and research populations that have been established in an effort to conserve the diversity within the breed. The aim of this study was to investigate the overall genetic diversity as well as similarities and differences within and between two conservation herds of the South African Nguni Cattle. Mean LD (r2) estimates were 0.413 ± 0.219 for Bartlow Combine and 0.402 ± 0.209 for Kokstad. Genome-wide average LD (r2) decreased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As expected, the N e in the studied commercial and Creole populations declined over generations. The N e estimation in Latin American Creole cattle is scarce; however, this parameter was reported for several indigenous and highly selected commercial cattle breeds, showing similar decay of N e over generations (Biegelmeyer et al., 2016; Dlamini et al., 2022; Garcia et al., 2023; Jin et al., 2022; Sargolzaei et al., 2008; Strucken et al., 2021; Sudrajad et al., 2016; Xu, Zhu, et al., 2019). Creole populations had an accelerated decline and presented lower values, consisting of a few individuals compared with dozens of animals for worldwide distributed breeds (Sargolzaei et al., 2008; Biegelmeyer et al., 2016; Campos et al., 2022; present work).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As expected, the N e in the studied commercial and Creole populations declined over generations. The N e estimation in Latin American Creole cattle is scarce; however, this parameter was reported for several indigenous and highly selected commercial cattle breeds, showing similar decay of N e over generations (Biegelmeyer et al., 2016; Dlamini et al., 2022; Garcia et al., 2023; Jin et al., 2022; Sargolzaei et al., 2008; Strucken et al., 2021; Sudrajad et al., 2016; Xu, Zhu, et al., 2019). Creole populations had an accelerated decline and presented lower values, consisting of a few individuals compared with dozens of animals for worldwide distributed breeds (Sargolzaei et al., 2008; Biegelmeyer et al., 2016; Campos et al., 2022; present work).…”
Section: Discussionmentioning
confidence: 88%
“…The conservation of animal genetic resources refers to measures taken to prevent the loss of genetic diversity in livestock populations, including the protection of breeds from extinction (FAO, 2007). Several countries, such as Argentina, Bolivia and Brazil, have established conservation plans to preserve Creole populations (da Silva Mariante, 1990a, 1990bMichiels et al, 2023). These plans are fundamental because endangered native populations are naturally adapted to the local environment and contribute a high proportion of the species genetic diversity.…”
mentioning
confidence: 99%
“…Other genes that were found to be associated with the ewe LWM in the present study have been reported as candidate genes for LW-related traits in different species. For example, A1CF, ZNF830, CCT6B and MYO10 were associated with residual feed intake in cattle [47][48][49], while the genes CTBP2 and AP2B1 have been linked to meat quality and lipid metabolism in pigs [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that signatures of selection spanning melanophilin ( MLPH ), melanocyte stimulating hormone receptor ( MC1R ), membrane‐associated transporter ( SLC45A2 ) and Ras oncogene family genes ( RAB17 , RAB37 ) were detected in African cattle breeds. These genes play a direct role in melanogenesis (Cieslak et al, 2011; Dlamini et al, 2022; Taye et al, 2018; Taye, Lee, Caetano‐Anolles, et al, 2017; Taye, Lee, Jeon, et al, 2017). A mutation in the MLPH gene in dogs, cats and rabbits is thought to disrupt the transportation of melanosomes to the outer edges of melanocytes (Philipp et al, 2005); it prevents the transfer of melanosomes into the keratinocytes, thus resulting in hairs of lighter colour (Demars et al, 2018; Ishida et al, 2006).…”
Section: Genomic Footprints Of Natural Selectionmentioning
confidence: 99%